ANALISIS PENGARUH FUNDAMENTAL TERHADAP PERGERAKAN NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA - Renny Mointi (Jurnal Bisnis dan Kewirausahaan, 2018)
The purpose of this research is to know the fundamental influence of inflation on rupiah exchange rate against US dollar or USD / IDR, Bank Indonesia interest rate against rupiah exchange rate against US dollar (USD / IDR), gross domestic product against the movement of the rupiah against the US dollar / USD / IDR. The analytical method used to know Influence of Inflation, Interest Rate to US dollar (USD / IDR), is by using multiple linear regression analysis. SPSS program version 17.0. The result of the research shows that inflation has a positive and significant effect on the movement of the rupiah against the US dollar (USD / IDR). The interest rates of Bank Indomesia affect the movement of exchange rate of American products and gross domestic product have positive and insignificant effect to US dollar (USD / IDR)